2010
DOI: 10.1002/pssc.200982425
|View full text |Cite
|
Sign up to set email alerts
|

ALD growth of Al2O3 on GaAs: Oxide reduction, interface structure and CV performance

Abstract: We have studied the effect of the trimethylaluminum (TMA) precursor on the reduction of surface “native” oxides from GaAs substrates using medium energy ion scattering spectroscopy (MEIS), X‐ray photoelectron spectroscopy (XPS) and electrical measurements. Our data show that after one single TMA pulse a substantial part of the native oxide is reduced and an oxygen‐rich aluminum oxide layer is formed. Al2O3 films grown with the normal atomic layer deposition cycles of TMA and water show that the growth rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is reported that weak Fermi‐level pinning results in a small frequency‐dependent flatband shift 10. The frequency dispersion of the accumulation capacitance is merely 8%, which indicates a good quality Al 2 O 3 /S–GaAs interface is obtained 11.…”
Section: Resultsmentioning
confidence: 94%
“…It is reported that weak Fermi‐level pinning results in a small frequency‐dependent flatband shift 10. The frequency dispersion of the accumulation capacitance is merely 8%, which indicates a good quality Al 2 O 3 /S–GaAs interface is obtained 11.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 2(a) shows a large accumulation capacitance frequency dispersion of 18.9% for SiO 2 /InP from the weak Fermi-level pinning at a certain D it (6.1 © 10 12 cm ¹2 eV ¹1 ). 34,35) This result shows that residual native oxides existed on InP only with HF in-situ cleaning and passivation. Figure 2(b) shows a smaller frequency dispersion of 14.2% for SiO 2 /S-InP.…”
Section: Resultsmentioning
confidence: 84%
“…Figure 3(a) shows a large accumulation capacitance frequency dispersion of 19% for SiO 2 /GaAs from the weak Fermi-level pinning by a certain extent of D it (5.24 © 10 12 cm ¹2 eV ¹1 ). 23,24) This result shows that residual native oxides existed on GaAs only with HF in situ cleaning and passivation. Figure 3(b) shows a smaller frequency dispersion of 12% for SiO 2 /S-GaAs.…”
Section: Resultsmentioning
confidence: 84%